The Development of the Effectiveness of Remote Work as Perceived by Employees and Managers - Wojtkowiak, Grzegorz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2023)
Objective: This article discusses how the effectiveness of remote work has developed and differences in how it is assessed by employees and managers. Two research questions are asked: 1) How do employees assess the impact of remote work tools on various aspects of operation? and 2) How do managers perceive and approach employee attitudes and opinions in this area?Research Design & Methods: Computed-Assisted Web Interviews (CAWI) were conducted with 500 respondents (employees of companies with international capital). The results were then discussed (interviews) with 14 middle and senior managers.Findings: Employees believed the technology and tools available had the most significant positive impact on innovation and organisation. In contrast, aspects related to communication and relationships had the lowest impact. Although manager’s comments related to the effectiveness scores were divided, they did not contradict one another.Implications / Recommendations: Based on the research, an attempt was made to distinguish key variables for managers. They include: work programming (rules, principles, control, KPIs), ensuring autonomy (freedom in organising work and decision-making, ensuring trust), maintaining relationships (including effective communication) and one’s own skills.Contribution: It is important to understand that there are differences in how employees and managers perceive effectiveness and task performance efficiency. Managers’ awareness of their employees’ opinions is vital, as the interviews show.